Streptococcus oralis endocarditis leading to central nervous system infection in pregnancy. Issue 2 (7th October 2021) - Wydall, S.; Durrant, F.; Scott, J.; Cheesman, K.
Summary: This report describes a challenging obstetric case in which septic emboli from Streptococcus oralis endocarditis subsequently led to central nervous system infection. There were delays in diagnosis as the patient presented with non‐specific symptoms of fever, diarrhoea and vomiting, initially suspected to be due to viral gastroenteritis and later SARS‐CoV‐2 infection. Antibiotics were commenced once gram positive cocci were isolated from a blood culture. The patient made no significant improvement despite antimicrobial therapy and subsequently developed a worsening headache and delirium. This deterioration was not rapidly recognised despite the use of a routine obstetric early warning score. However, a diagnosis of meningitis was made once the potential severity of the patient's condition was recognised and Streptococcus oralis was identified in cerebrospinal fluid and blood cultures. Bacterial endocarditis was diagnosed following transthoracic echocardiography. The patient improved with optimised antimicrobial therapy and delivered a healthy baby. This example highlights how non‐specific symptoms can be caused by rare and life‐threatening illnesses, and emphasises that early warning scores might not easily identify neurological deterioration in obstetric patients.